Temporal Trends in Complex Percutaneous Coronary Interventions - Kheifets, Mark; Vons, Shelly Abigail; Bental, Tamir; Vaknin-Assa, Hana; Greenberg, Gabriel; Samara, Abed; Codner, Pablo; Wittberg, Guy; Talmor Barkan, Yeela; Perl, Leor; Kornowski, Ran; Levi, Amos (Frontiers in Cardiovascular Medicine, 2022)
Background: Accumulated experience combined with technological advancements in percutaneous coronary interventions (PCI) over the past four decades, has led to a gradual increase in PCI utilization and complexity. We aimed to investigate the temporal trends in PCI complexity and the outcomes of complex PCI (C-PCI) in our institution. Methods: We analyzed 20,301 consecutive PCI procedures performed over a 12-year period. C-PCI was defined as a procedure involving at least one of the following: Chronic total occlusion (CTO), left main (LM), bifurcation or saphenous vein graft (SVG) PCI. Four periods of 3-year time intervals were defined, (2008-10, 2011-13, 2014-16, 2017-19), and temporal trends in the rate and outcomes of C-PCI within these intervals were studied. Endpoints included mortality and major adverse cardiac events [MACE: death, repeat myocardial infarction (re-MI), and target vessel revascularization (TVR)] at 1 year. Results: 5647 (27.8%) C-PCI procedures were performed. The rate of C-PCI has risen significantly since 2017 (p<0.01), driven mainly by bifurcation and LM interventions (p<0.01). At 1-year, rates of death, re-MI, TVR and MACE, were all significantly higher in the C-PCI group (p<0.001 for all), as compared to the non-complex group. C-PCI preformed in the latter half of the study period (2014-2019) were associated with improved 1-year TVR (p=0.01) and MACE (p=0.001) rates compared to the earlier period (2007-2013). Death rate had not significantly declined with time. Conclusions: In the current cohort, we have detected a temporal increase in PCI complexity coupled with improved 1-year clinical outcomes in C-PCI.